The Effect of Work Conflict, Work Environment, and Work Stress on Employee Work Satisfaction at Representative Office Agency of Population and Family National Planning (BKKBN) Sumatera Utara - Purnama, Nadia Ika; Rialdy, Novien; Afriyani, Merry (Journal of International Conference Proceedings, 2023)
The purpose of this study is to partially examine the variables of labor conflict, work environment, and work stress that affect employee job satisfaction, and the simultaneous effects of labor conflict, work environment, and work stress on employee job satisfaction. is to decide The research type used in this study is an associative and quantitative approach. The sampling method uses a saturated sample of 84 full-time employees data collection techniques Â interviews, documentation studies and questionnaires. The data analysis techniques in this study used classical acceptance tests and multiple regression analysis. As a result, we found that the inconsistent variables partially negatively affected job satisfaction and had a small effect. Working environment variables can have a large positive impact on employee job satisfaction.Â Fluctuating work stress has a small but positive impact on employee job satisfaction, simultaneously variables of work conflict, work environment and work stress affects employee job satisfaction.